Endovascular therapy beyond 24 hours for anterior circulation large vessel occlusion or stenosis in acute ischemic stroke: a retrospective study - Wen, An; Cao, Wen-feng; Zhao, Chao; Wu, Ling-feng; Zhou, Yong-liang; Xiang, Zheng-bing; Rao, Wei; Liu, Shi-min (Frontiers in Neurology, 2023)
Background: To assess the clinical and safety outcomes of endovascular treatment (EVT) administered more than 24 hours after the onset of symptoms in patients with acute ischemic stroke resulting from anterior circulation large-vessel occlusion or stenosis (AIS-ACLVO/S).We enrolled consecutive AIS-ACLVO/S patients who received EVT in our hospital between January 2019 and February 2022 and divided them into two groups based on the time from AIS onset to EVT: EVT < 24 h group and EVT >24 h group. The successful reperfusion (modified thrombolysis in cerebral infarction, [mTICI] ≥2b), 90-day modified Rankin Scale score (mRS), intracranial hemorrhage (ICH), and symptomatic ICH (sICH), as well as mortality, were analyzed in the two groups of patients.Results: A total of 239 patients were included in the study, with 214 patients in the EVT < 24 h group (67.8 ± 0.8 years, 126 males) and 25 patients in the EVT > 24 h group (62.80 ± 2.0 years, 22 males). Both groups were similar in terms of hypertension, diabetes history, responsible vessels, and Alberta stroke program early computed tomography scores (P>0.05). However, the EVT < 24 h group had significantly higher age, history of atrial fibrillation, proportion of patients receiving intravenous thrombolysis, and NIHSS scores before EVT than the EVT > 24 h group. AIS etiology differed between the groups, with more cases of large artery atherosclerosis in the EVT > 24-h group and more cases of cardioembolism in the EVT < 24-h group. Successful reperfusion (mTICI ≥ 2b), ICH, and sICH were similar between the groups. The 90-day functional independence rate (mRS ≤ 2) was significantly higher in the EVT > 24-h than in the EVT < 24-h group (80% vs. 39.7%, P < 0.001), while the 90-day mortality rate was lower in the EVT > 24-h group (0% vs. 24.8%, P < 0.001).In our study, we found that EVT beyond 24 hours of symptom onset in patients selected with multimodal MR screening, was associated with high functional independence rates and low mortality. Larger or randomized studies are needed to confirm these findings.